A Review of Literatures on Islamic Finance Between 2006 - 2016 - Muhammad Ridhwan Ab. Aziz; Ahmad Azwan Meor Hashim; Nurul Saadah Wan Mohd Salleh (PKP Open Journal System, 2024)
Non-Indexed Publication